Workshop LKPD untuk Pembelajaran dengan Metode Problem Based Learning (PBL) - Yulianti, Dwi; Insani, Marzius; Chandra, Lala Dyah; Iskandar, Iskandar (Universitas Lampung, 2025)
The purpose of this service activity is to improve the quality and competence of teachers through training in making LKPD for learning with the problem based learning (PBL) method. The role of teachers in the digital era requires high creativity to form students who are able to think critically. In its implementation, students do not receive appropriate support in the national curriculum applied in honing critical thinking skills. In an effort to improve students' critical thinking skills. Educators must be able to develop appropriate learning models so that students gain meaningful experiences. LKPD has components and elements that are able to increase student participation in the learning process. In addition, in LKPD, model development is also needed to achieve the expected goals in the learning process. One of the models that can be used is problem-based learning (PBL). The PBL model is a systematic model and is able to develop and test critical thinking skills in a continuous manner. Workshop on making LKPD for learning with the problem based learning (PBL) method so that educators can try to improve students' critical thinking skills.